A Contrastive Analysis on Taboo Words in English And Minangkabau Language - Fachri Yunanda; Saptari Wibowo; Jimmi Amanda Aritonang (RIRAI Publisher, 2022)
This study focuses on a contrastive analysis of taboo words in English and Minangkabau, an Indonesian language spoken in Sumatera Barat. This study aimed to identify, categorize, and compare the differences between taboo terms used in Minangkabau and English. This study's research methodology was descriptive qualitative. Three procedures were used to carry out this study. The data for taboo terms in English was first prepared using literature, film, and native speakers staying in Medan, Sumatera Utara, whereas the data for taboo words in Minangkabau was prepared using literature, research, and local speakers in Bonjol, Pasaman, Sumatera Barat. Second, talking to several informants on the meaning of the banned terms to gain the full meaning. Third, the Wardhaugh theory was used to examine all the data, and the Lado Theory was used to compare the data to identify similarities and contrasts. According to the study's findings, there are five categories of taboo words in the Minangkabau language, including those that are connected to sex, animals, death, and excrement. They were distinct from the English words for sex, animal functions, human bodily parts, death, excrement, and religion.